Light and scanning electron microscopic studies on subcommissural organ of the pig - KUMAR, P; KUMAR, PAWAN (The Indian Journal of Animal Sciences, 2012)
The subcommissural organ (SCO) of pig located on the ventral aspect of posterior commissure was constituted by an ependyma and a hypendyma. The pseudostratified columnar ciliated ependyma of SCO comprised 8–11 rows of round, oval to elongated type-I and type-II nuclei. Less basophilic type-I and darkly stained type-II nuclei were categorised on the basis of distribution of nuclear chromatin and staining affinity. The hypendyma contained hypendymal cells, micro- and macro-glial cells, blood capillaries and nerve fibres. The neurosecretory substance in the form of small, pink structures was mainly localised towards the supranuclear portion of the ependyma, free ventricular surface and lumen of blood capillaries. Scanning electron microscopy revealed ciliated and non-ciliated apical spherical protrusions along with tufts of cilia. A few apical spherical protrusions possessed small microvilli like structure.